2015
DOI: 10.1080/1331677x.2015.1043777
|View full text |Cite
|
Sign up to set email alerts
|

The importance of government incentives for housing savings in Croatia

Abstract: This article analyses the determinants of housing savings (the contractual saving scheme) in Croatia by applying Vector Autoregression (VAR) methodology on monthly data for the period 2000-2013. The results show that the selected macroeconomic indicators (wages, interest rate, stock exchange index-CROBEX, availability of loans and unemployment rate) do not influence the housing savings market dynamics. Moreover, the housing savings system proves to be resilient to economic downturn. On the other hand, the find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Scientific research on the relationship between investment, savings and economic growth for the countries of the Western Balkans is generally very rare. The one standing out is Bađun & Franić (2015), who investigated the determinants of an extremely important category of housing savings in Croatia for the period 2000-2013. The results of the research showed that the analyzed variables: salaries, interest rate, stock exchange index, availability of loans and unemployment rate, do not affect the volume and dynamics of housing savings.…”
Section: Grosssave Grossinvmentioning
confidence: 99%
“…Scientific research on the relationship between investment, savings and economic growth for the countries of the Western Balkans is generally very rare. The one standing out is Bađun & Franić (2015), who investigated the determinants of an extremely important category of housing savings in Croatia for the period 2000-2013. The results of the research showed that the analyzed variables: salaries, interest rate, stock exchange index, availability of loans and unemployment rate, do not affect the volume and dynamics of housing savings.…”
Section: Grosssave Grossinvmentioning
confidence: 99%